Dans les archives françaises de Raoul&#8239Hausmann&#8239: l’autotraduction inachevée de Hylé II et la recherche d’une forme textuelle en mouvement - Hélène Thiérard (Continents manuscrits)
In his mature literary work, Hylé II, written in German between 1933 and 1958, the former Berlin Dadaist Raoul Hausmann looks back on his years of exile in Ibiza; the article proposes a genetic study of the unfinished self-translation into French of Hylé II. The analysis reconstructs how the self-translation initiated in 1937 evolves soon after into a form of free rewriting, and jeopardises the completion of the German project, before being abandoned around 1945. This failed attempt is to be understood first of all as a crucial stage in Raoul Hausmann’s development as a bilingual writer after the war, when he chose France as his new homeland. The French self-translation must also be examined in relation to the core project of Hylé II, namely the production of a textual form in motion. Reintegrating the self-translation within the original text, in a late phase of its genesis, is one of the many textual strategies used by Hausmann to destabilise the traditional notion of text, a gesture closely akin to the attacks of the historical avant-gardes on the category of work (œuvre) and the institution of art.